PERSPECTIVES OF USING OF EVAPORATIVE COOLING IN REFRIGERATION ENGINEERING - Doroshenko A.V.; Lisohurska O.A. (Problems of the Regional Energetics, 2013)
The concept of creation of multi-stage evaporative coolers of gases and liquids based on multi-channel monoblock polymer structures was developed. The indirect types of coolers in normal and regenerative options are used as the basic elements in them. Natural limit of the cooling in such systems is the dew point of outside air, which significantly enhances the possibilities of the evaporative cooling technology in general, and allows us to solve a number of problems of the refrigeration and air conditioning equipment with a significant reduction of energy consumption for the process. Particular attention is paid to the problem of water vapor recondensation in the transition to multi-stage evaporative coolers. The theory of joint heat and mass transfer in indirect evaporative cooling was examined. The principle of design of individual monoblocks, as well as multi-stage blocks, was developed and recommendations to the design of a new generation of evaporative coolers were made. Preliminary analysis of the possibilities of the evaporative coolers applying to the solution of problems of air conditioning was made.